Content of Fatty Acids in Callus Cultures of Endemic Ajuga vestita BOISS. - Mehmet Yusuf Orcan; Pınar Orcan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Ajuga L., a member of the Lamiaceae family, is one of the most popular species due to its medicinal, decorative, and pharmacological properties. One of them is Ajuga vestita BOISS. which is endangered and placed in the "Endangered (EN)" category. In the present study, using in vitro tissue culture techniques, Ajuga vestita BOISS. seeds were germinated in hormone-free 1/4 MS medium, and callus were regenerated from leaf explants of germinated seeds in 1/1 MS medium containing BAP (benzylaminopurine) and Kin (kinetin). It was aimed at comparatively examining the fatty acid content of Ajuga vestita BOISS. callus. When the fatty acid content of the callus obtained from the control (hormone-free), BAP, and Kin media were examined, major saturated fatty acid amounts were palmitic acid in all three extracts (59.137%, 38.836%, and 24.295%) for control, BAP, and Kin respectively. The major unsaturated fatty acid amounts were octadecanoic acid (21.097%, 32.283%) for control and BAP, respectively, and linoleic acid (21.209%) for Kin considering that high amounts of unsaturated fatty acids make the plants more reliable in terms of health, the higher amount of unsaturated fatty acid content determined in the Kin extract in our study compared to the control will shed light on future studies in this sense that can be done with tissue culture techniques.